Distinguished Filipino women testing and applying models of talent development and exceptional achievement - Tantengco, Myra Trinidad Timtiman (2009)
An art-therapy workshop on fourteen adolescents with depressive delinquent behaviors was conducted. Data were gathered on the characteristics of the respondents based on four personal abilities, their characteristics after the implementation of the workshop, and the significant differences between the respondents pretest and posttest results. The results of the study showed respondents disclosing their thoughts, relating past experiencs, accepting mistakes and accepting commendations as the most difficult tasks. Respondents did not show any reaction before the workshop and no willingness to improve themselves. The study concludes that the art-therapy workshop facilitated respondents' self-expression, helped cultivate their identity, strengthen their self-confidence and enabled them to make achievable goals and short term plans.
Thesis (M.A. Special Education)--University of the Philippines, Diliman.
Best thesis.
Keywords: Women in politics -- Philippines; Women government executives -- Philippines; Women in mass media -- Philippines; Businesswomen -- Philippines; Women entrepreneurs -- Philippines; Women -- Philippines -- Social conditions; Women -- Philippines -- Biography